2022
DOI: 10.1253/circj.cj-21-0889
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Non-Atrial Fibrillation Bradyarrhythmias Treated With a Ventricular Demand Leadless Pacemaker Compared With an Atrioventricular Synchronous Transvenous Pacemaker ― A Propensity Score-Matched Analysis ―

Abstract: Background: Implanting a ventricular demand leadless pacemaker (VVI-LPM) for patients with non-atrial fibrillation (AF) bradyarrhythmias such as sick sinus syndrome (SSS) or high-grade (i.e., second-or third-degree) atrioventricular (AV) block is not recommended unless they have limited vascular access or a high infection risk; nevertheless, an unexpectedly high number of VVI-LPM implantations have been performed. This study investigated the clinical outcomes of these unusual uses. Methods and Results:This stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…In a smaller study of 53 patients, who were also matched for age and sex, Beurskens et al described worsening of TR in 43% with LLPM versus 38% patients with conventional transvenous systems but this difference was not significant 11 . Similarly, in a propensity score matched analysis of 193 patients with LLPMs and conventional devices, significant TR was more prevalent in transvenous than leadless devices (12% vs. 9%), but again, this difference was not significant 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a smaller study of 53 patients, who were also matched for age and sex, Beurskens et al described worsening of TR in 43% with LLPM versus 38% patients with conventional transvenous systems but this difference was not significant 11 . Similarly, in a propensity score matched analysis of 193 patients with LLPMs and conventional devices, significant TR was more prevalent in transvenous than leadless devices (12% vs. 9%), but again, this difference was not significant 24 …”
Section: Discussionmentioning
confidence: 99%
“…9%), but again, this difference was not significant. 24 Given the limited evidence, it seems possible that LLPMs may better preserve tricuspid valve function after device implantation as unlike transvenous leads, they do not permanently cross the valve.…”
Section: Impact On Tr Of Llpms Versus Conventional Transvenous Pacema...mentioning
confidence: 99%
“…LPs implantation after cardiac implantable electronic device (CIED) infection, was successful and reduced recurrence rates [99][100][101][102][103]. Consistently, in the few studies comparing infective complications in LPs and PM patients, PM showed higher rates of these complications [104][105][106].…”
Section: Leadless Pacemakermentioning
confidence: 75%
“…Despite the absence of leads crossing the TV, LPMs with lengths of 42 mm for the Nanostim, and with lengths of 25.9 mm for the Micra, still have the potential to interact with the valvular apparatus. The aggravation of TR was observed in 12% of patients with LPMs during the 48 month follow-up when compared with 9% of patients with TPMs [ 63 ]. However, an age- and sex-matched analysis showed a higher increase in the TR severity in patients with TPMs than in those with LPMs [ 64 ], and the LPMs had the advantage of reducing the TR effective regurgitant orifice area, compared with conventional leads 1 month after the device implantation [ 65 ].…”
Section: Leadless Ventricular Pacemakersmentioning
confidence: 99%
“…It remains to be seen whether non-AF patients will benefit more from DDD-TPMs than VVI-LPMs. A propensity-matched analysis indicated that VVI-LPMs for non-AF bradyarrhythmias significantly increased the rate of heart-failure-related rehospitalization at the 48 month follow-up compared with the use of DDD-TPMs, and a higher but not significant all-cause mortality was observed in patients with VVI-LPMs [ 63 ].…”
Section: Selection Strategy For Lpms Vs Tpmsmentioning
confidence: 99%